Iran J Pathol 2019
DOI: 10.30699/ijp.14.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Renal Capillary Hemangioma Mimicking Urothelial Carcinoma, A Case Report and Review of the Literature

Abstract: Renal hemangioma is a rare tumor which can be capillary or cavernous. There have been less than 30 renal capillary hemangioma cases reported in the English literature. Herein we will report a case of renal hemangioma which was detected in a 74-year-old man operated with the impression of urothelial carcinoma of hilum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…At present, most patients with renal venous malformation have no obvious symptoms, and they are only found by chance during physical examination. 13 A few patients may have hematuria (microscopic hematuria or gross hematuria), mostly intermittent hematuria, which is caused by the rupture of vascular epithelium of renal pelvis and calyceal mucosa, and blood clots may appear in patients with a large amount of hematuria, even endangering life. 7 Some patients also have low back pain (slight pain or renal colic), which is caused by blood clot blocking the ureter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, most patients with renal venous malformation have no obvious symptoms, and they are only found by chance during physical examination. 13 A few patients may have hematuria (microscopic hematuria or gross hematuria), mostly intermittent hematuria, which is caused by the rupture of vascular epithelium of renal pelvis and calyceal mucosa, and blood clots may appear in patients with a large amount of hematuria, even endangering life. 7 Some patients also have low back pain (slight pain or renal colic), which is caused by blood clot blocking the ureter.…”
Section: Discussionmentioning
confidence: 99%
“…At present, most patients with renal venous malformation have no obvious symptoms, and they are only found by chance during physical examination. 13 A few patients may have hematuria (microscopic hematuria or gross hematuria), mostly Figure 1. CTU: A plain scan showed that the left renal pelvis and calyces showed a slightly high-density shadow, with a CT value of about 62HU, a size of about 2.6 cm*1.5 cm, and blurred edges, mainly in the middle and lower poles of the renal pelvis and calyces B and C. Enhanced scan showed that mild-to-moderate enhancement was found at the edge of the lesion; after enhancement, the left renal cortex in the lower pole was diffusely low enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific site of hemangioma is prone to serious complications, such as an intracranial hemangioma rupture causing intracerebral hemorrhage and an intestinal hemangioma rupture causing gastrointestinal hemorrhage. According to the published literature, there have been less than 40 cases of renal capillary hemangioma reported ( 12 ). There have also been reports of renal rupture and bleeding ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, renal hemangiomas are seen in the context of end-stage renal disease, polycythemia, or hypertension [5][6][7][8][9]. Rare cases arising in the vicinity of RCCs have been reported, as well as cases with syndromic associations such as Klippel-Trenaunay and Sturge-Weber disease [8,[10][11][12][13][14].…”
Section: Hemangiomamentioning
confidence: 99%
“…Immunohistochemical analysis using cytokeratins, PAX8, CD10, and CAIX should resolve the distinction between RCC and hemangioma. Other neoplasms that should be ruled out include angiosarcoma (which typically shows increased cytologic atypia, mitotic activity, and necrosis), anastomosing hemangioma (which usually displays lobular growth of sinusoidal vascular spaces with prominent intervening stroma), and angiomyolipoma (especially as entrapped adipocytes may be seen in hemangiomas, producing an angiomyolipoma-like appearance; immunohistochemistry with melanocytic markers usually easily distinguishes these two entities) [12,15].…”
Section: Hemangiomamentioning
confidence: 99%